Lewin, Herbert (audio interview #2 of 2) - Lewin, Herbert (1906 - 1987); Andriesse, Ann, interviewer
INTERVIEW DESCRIPTION - This interview was conducted in the home of George Badenhausen, Lewin's friend. Occasionally, Badenhausen comments on the subjects being discussed or responds when prompted by Lewin. 5/23/1985